Contemporary International Criminal Law Issues Contributions in Pursuit of Accountability for Africa and the World - Sendze, Takeh B. K.; Adeboyejo, Adesola; Morrison, Howard; Ugwu, Sophia (The Hague : T.M.C. Asser Press : Imprint: T.M.C. Asser Press, 2023)
This book critically analyses diverse international criminal law (ICL) issues in light of recent developments in the international criminal justice system following the pursuit of accountability in Africa and around the world. It gives a scholarly analysis of issues pertaining to ICL and the pursuit of accountability in Africa by way of several topics including universal jurisdiction in Africa, Boko Haram in Nigeria, the legitimacy of the ICTR, the law of genocide committed against the Herero and Nama peoples, the African perspective on international co-operation in criminal matters, the Malabo Protocol, and whether an African Regional Court is a viable alternative to the ICC. Further discussed are other aspects of ICL, such as prosecuting sexual and gender-based crimes at the ICC, sexual and gender-based crimes perpetrated against men, guilty pleas within ICL and slavery within international criminal justice. With this, the book also refers to the jurisprudence of several international courts and tribunals including the ICTR, the ICTY, the SCSL, the ICC, the ECCC, the KSC, and the STL. This timely contributed volume updates international criminal law experts, practitioners, academics, human rights activists and other stakeholders on contemporary developments in ICL and provides recommendations that address accountability for mass atrocity crimes and ideas for strategic ICL litigation at the national, international, regional and sub-regional levels. It will prompt constructive exchanges on what can be improved in prosecuting mass atrocity crimes around the world. Takeh B.K. Sendze is an Advocate and Legal Officer with the United Nations International Residual Mechanism for Criminal Tribunals in Arusha, Tanzania. Adesola Adeboyejo is a Trial Lawyer at the International Criminal Court. Sir Howard Morrison QC is a former International Judge and an Associate Tenant at Doughty Street Chambers in London, United Kingdom. Sophia Ugwu is a Solicitor and Advocate who founded the Centre for African Justice, Peace and Human Rights in The Hague, The Netherlands.
Chapter 1. Introduction -- Part I. International Criminal Law: Looking Through the African Lens -- Chapter 2. The Scope and Application of Universal Jurisdiction: A Synopsis of African States' Positions and Proposals during Plenary Sessions in the Sixth Committee of the United Nations General Assembly -- Chapter 3. Bring Justice to Our Girls? The ICC Inquiry into Boko Haram in Nigeria.-Chapter 4. The Legitimacy of the International Criminal Tribunal for Rwanda (ICTR) -- Chapter 5. The Law of Genocide and Atrocities Committed Against the Herero and Nama Peoples -- Chapter 6. Horizontal and Vertical International Co-operation in Criminal Matters: An African Regional and Sub-regional Perspective -- Chapter 7. Is an African Regional Court a Viable Alternative to the International Criminal Court? A Neutral View -- Part II. International Criminal Law beyond the African Region -- Chapter 8. Breaking Binaries and Honing in on Harms: Inclusive Approaches Towards Sexual and Gender-based Crimes -- Chapter 9. Sexual and Gender-based Violence: What Legacy for the New ICC Prosecutor? -- Chapter 10. The Marginalization of Slavery in International Criminal Justice: Untapping Its Potential in the Fight against Modern Slavery -- Chapter 11. The Evolution and Practice of Guilty Pleas in International Criminal Law.
Keywords: International criminal law; Humanitarian law; Human rights; International law; International Criminal Law; International Humanitarian Law, Law of Armed Conflict; Human Rights; Public International Law